Effects of smoking on the urine excretion of oral51Cr EDTA in ulcerative colitis. Issue 5 (1st May 1998) - Benoni, C; Prytz, H
Abstract : Background —Smokers have a reduced risk and ex-smokers an increased risk of ulcerative colitis (UC). Stopping smoking often precedes onset and relapses. Smoking reduces the 24 hour urine excretion of oral chromium-51 labelled EDTA in healthy individuals. Aims —To estimate the effects of smoking on the urine excretion of oral 51 Cr EDTA in well characterised patients with UC. Subjects —Sixteen smoking and 16 non-smoking patients with UC in remission were studied. The non-smokers had never smoked. Most were taking 5-aminosalicylic acid. No patient took steroids or immunosuppressants. The control group comprised 25 smoking healthy volunteers and 25 who had never smoked. The median cigarette consumption was equal in the patients and volunteers. Methods —The 24 hour urine excretion of oral 51 Cr EDTA was measured and the results were correlated with smoking habits, number of cigarettes, and disease extent. Results —Patients with UC had significantly higher 24 hour urine recoveries than healthy controls (p=0.04). This difference was more pronounced when patients who smoked were compared with healthy smokers (p=0.005) No significant differences were found when comparing non-smoking patients with non-smoking controls or when comparing smoking and non-smoking patients. Urine recoveries did not correlate with number of cigarettes or disease extent. Smoking was more prevalent in patients with a more limited disease extent (p=0.033). Conclusions —Effects of smoking on the urine excretion of 51 Cr EDTA in health were abolished by the presence of UC. The protective effects of smoking in established UC are not due to a moderating effect of smoking on intestinal permeability.